Facilitating and motivating factors for reporting reprehensible conduct in care: A study among nurse practitioners and physician assistants in the Netherlands. Issue 4 (20th August 2020) - Kuilman, Luppo; Jansen, Gerard; Mulder, Laetitia B.; Roodbol, Petrie
Abstract: Rationale, aims and objectives: The aims of this study are as follows: (a) to establish whether a relationship exists between the importance that healthcare professionals attach to ethics in care and their likelihood to report reprehensible conduct committed by colleagues, and (b) to assess whether this relationship is moderated by behavioural control targeted at preventing harm. Method: In this cross‐sectional study, which was based on a convenience sample (n = 155) of nurse practitioners (NPs) and physician assistants (PAs) in the Netherlands, we measured ethics advocacy (EA) as a motivating factor (reflecting the importance that healthcare professionals attach to ethics and care) and "behavioral control targeted at preventing harm" (BCPH) as a facilitating factor. "Reporting reprehensible conduct" (RRC) was measured as a context‐specific indicator of whistleblowing intentions, consisting of two vignettes describing morally questionable behaviour committed by colleagues. Results: The propensity to report reprehensible conduct was a function of the interaction between EA and BCPH. The only group for which EA predicted RRC consisted of individuals with above‐average levels of perceived BCPH. Conclusion: The results suggest that the importance that healthcare professionals attach to ethical aspects in care is not sufficient to ensure that they will report reprehensible conduct. Such importance does not induce reporting behaviour unless the professionals also perceive themselves as having a high level of BCPH. We suggest that these insights could be helpful in training healthcare providers to cope with ethical dilemmas that they are likely to encounter in their work.